125 Cardiac metabolic flexibility and myocardial substrate utilisation in response to pharmacological stress in type 2 diabetes. (4th June 2021) - Athithan, Lavanya; Parke, Kelly S; Ladwiniec, Andrew; Adlam, David; Gulsin, Gaurav S; Sian, Manjit; Marsh, Anna-Marie; McCann, Gerry P; Levelt, Eylem
Abstract : Background: Efficient matching of energy supply to demand is essential for maintaining normal cardiac function. Altered cardiac metabolism may contribute to the development of cardiac dysfunction by impairing metabolic flexibility in type 2 diabetes (T2D). Utilising simultaneous coronary sinus (CS) and aorta blood sampling and cardiac magnetic resonance imaging (CMR), we aimed to evaluate the effect of T2D on myocardial substrate preferences in response to acute increases in cardiac workload and the effects on contractile function. Methods: Eligible participants without obstructive coronary artery disease (>50% luminal coronary artery stenosis on coronary angiography) underwent transmyocardial arteriovenous blood sampling. Metabolites in paired coronary sinus and arterial samples were quantified to determine myocardial fuel selection at rest and during a stress protocol with intravenous dobutamine. Fatty acid (FA), glucose, 3-hydroxybutyric acid (3HBA) and lactate utilisation at rest and haemodynamic stress was calculated as an extraction fraction % (EF). Participants underwent dobutamine stress multiparametric CMR imaging at 3.0 Tesla (Skyra, Siemens, Germany) on a separate visit within 21 days to quantify cardiac volumes, function and perfusion. Results: Two thousand and sixty-one participants were screened and due to stringent inclusion and exclusion criteria for this mechanistic study, three T2D patients and five matching controls were enrolled. Baseline demographics and glycometabolic results are documented in table 1 . Mean 3-HBA changes calculated as extraction fraction at stress and rest are illustrated in figure 1 . Table 2 shows the major echocardiographic and CMR results. There were no significant differences in FA or glucose uptake between T2D patients and controls at rest or stress. 3HBA EF was significantly increased in T2D during stress (25.04% vs - 5.31%, p=0.007). Conclusions: We demonstrate for the first time in vivo that the diabetic heart switches to ketone bodies during increased workloads as a significant fuel source. At present, it is unknown whether enhanced ketone body metabolism in T2D is beneficial, maladaptive, or a bystander. As the energetic properties of ketones are favourable, increased myocardial ketone oxidation could be an adaptive change designed to compensate for defects in myocardial energy metabolism in diabetes. Further, larger studies are warranted.Funding acknowledgement: This research was funded by the British Heart Foundation Clinical Research Training Fellowship and the Wellcome Trust on a Seed Grant Conflict of Interest: None